2023
DOI: 10.3390/s23146437
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study of Bridge Expansion Joint Damage Based on Natural Frequency

Abstract: In this paper, three studies on modal bridge expansion joints were conducted through experiments. The advantages and disadvantages of acceleration and fiber optic strain sensors in the tested modal expansion joints were compared. Secondly, the variation in the natural frequency of the modal bridge expansion joints at different concrete curing periods was investigated. Finally, the effect of damage on natural frequency in different parts (the center beam, the support bar, and concrete in the anchorage zone) of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Zhang et al [17] used an expectation maximization algorithm method to optimize the initial parameters of EJs and applied the method to the design of EJs for a long-span bridge. Li et al [18] analyzed the local damage effect on the natural frequencies of EJs, including the center beam, support beam, and concrete anchorage zone, and found that the natural frequencies of the center and support beams decreased with the increasing local damage.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al [17] used an expectation maximization algorithm method to optimize the initial parameters of EJs and applied the method to the design of EJs for a long-span bridge. Li et al [18] analyzed the local damage effect on the natural frequencies of EJs, including the center beam, support beam, and concrete anchorage zone, and found that the natural frequencies of the center and support beams decreased with the increasing local damage.…”
Section: Introductionmentioning
confidence: 99%
“…Bridge expansion joints are critical components in infrastructure, but they are not without their challenges [3]. Current issues in the field of bridge expansion joints include premature wear and deterioration [4], which often result from exposure to harsh environmental conditions such as heavy rainfall, temperature fluctuations, and the presence of corrosive agents [5].…”
Section: Introductionmentioning
confidence: 99%